2017
DOI: 10.1186/s40657-017-0084-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparing vocal structures of the parasitic and nonparasitic groups in Cuculinae

Abstract: Background: Avian brood parasitism is a breeding strategy in which brood parasites lay their eggs in the nest of other species. This behavior is closely related to aspects of the biological evolution of the parasitic species such as reduced female body size and plumage color polymorphism. However, not much is known whether it is associated with the evolution of vocalization. Methods:We collected samples of the typical male calls of 67 species belonging to the sub-family Cuculinae. Using the calls, we measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…), utilize a song that, although stereotyped, is important during the breeding season (Kroodsma & Miller, ). Call features always served as an important basis for interspecies classification in different cuckoo species (Kim, Lee, & Yoo, ; Xia, Liang, Carey, & Zhang, ). Although it is tacitly assumed that cuckoo vocalizations during the breeding season serve as a means of mate attraction (King, ; Xia et al, ), this crucial assumption remains untested empirically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), utilize a song that, although stereotyped, is important during the breeding season (Kroodsma & Miller, ). Call features always served as an important basis for interspecies classification in different cuckoo species (Kim, Lee, & Yoo, ; Xia, Liang, Carey, & Zhang, ). Although it is tacitly assumed that cuckoo vocalizations during the breeding season serve as a means of mate attraction (King, ; Xia et al, ), this crucial assumption remains untested empirically.…”
Section: Discussionmentioning
confidence: 99%
“…), utilize a song that, although stereotyped, is important during the breeding season (Kroodsma & Miller, 1996). Call features always served as an important basis for interspecies classification in different cuckoo species (Kim, Lee, & Yoo, 2017;Xia, Liang, Carey, & Zhang, 2016).…”
Section: Is the Function Of The Male Call To Attract Females?mentioning
confidence: 99%
“…Such a function would enable female cuckoos to benefit from reducing their egg rejection rate through distraction of the attention of hosts (York and Davies, 2017). Other aspects of female cuckoo calls remain unquantified in the peer-review literature (Liang, 2017;Kim et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Some brood parasites also have thicker eggshells ( Brooker and Brooker 1991 ), which can protect the parasitic egg from damage by hosts or other parasites. It has also been found that parasitic cuckoos have less complex and lower frequency vocalizations, which might travel better through their large breeding rages ( Kim et al. 2017 ).…”
Section: The Study System: Avian Brood Parasitismmentioning
confidence: 99%